Incidence Of Helicobacter Pylori Infection in Association With ABO Blood Groups - Zehra, Amina; Sabir, Maimoona; Sarwar, Sumaira; Ishfaq, Afsheen; Ahmad, Kishmain; Saleem, Afshan (Journal of Rawalpindi Medical College, 2024)
Objective: The study aimed to investigate the association between ABO blood groups and helicobacter infection. Method: 150 participants, including 93 females and 57 males between the age group of 18-60 years, were involved in the study. A sample of 3 ml blood was collected and screened against H. pylori antibodies (IgG) by H. pylori rapid diagnostic kit. ABO and Lewis antigen phenotypes were determined with a macroscopic agglutination technique. Results: According to the study’s findings, there were 55.42% women (46/83) and 44.5% men (37/83) among the 83 seropositive patients, while 70.14% women (47/67) and 29.85% men (20/67) were found among the 67 seronegative patients. The findings of this study reveal that those with the blood groups O+ and B+ have an estimated 25.3% (21/83) higher risk of H. pylori infection, whereas when seronegative individuals were investigated, it was discovered that blood groups 0+ were also leading, 28.4% (19/67), indicating that there was no significant difference between H. pylori seropositive and seronegative patients (p-value = 0.5146). Other factors, such as gender and family history, did not significantly affect the incidence of H. pylori. Conclusion: It was concluded from the study that no significant difference was observed between trends of H. pylori seropositive patients and seronegative individuals having different blood groups. Keywords: ABO Blood Group, Peptic Ulcer, Seronegative Pyloric patients, Seropositive Pyloric patients.